Comparing L1 and L2 organizational patterns in the argumentative writing of Japanese EFL students - Hirose, Keiko (Journal of second language writing, 2003)
The relationship between first language (L1) and second language (L2) writing has attracted the attention of L2 writing researchers. Recent studies have pointed to not only differences but also similarities between L1 and L2 writing. The present study compared L1 (Japanese) and L2 (English) organizational patterns in the argumentative writing of Japanese EFL student-writers. The study made within-subject comparisons of L1 and L2 compositions in terms of organizational patterns, organization scores, and overall quality. Student perceptions of L1 and L2 organization were also investigated by incorporating their comparisons of their own L1/L2 compositions into the analysis. The results revealed that (a) a majority of students employed deductive type organizational patterns in both L1 and L2; (b) despite similarities between L1 and L2 organizational patterns, L2 organization scores were not significantly correlated with L1 organization scores; (c) L2 composition total and organization scores differed significantly from those of L1; and (d) some students evidenced problems in organizing both L1 and L2 texts. Possible implications of the results are discussed as they pertain to research, pedagogy, and the dispelling of stereotypes about Japanese and English rhetoric.